MANAJEMEN PROGRAM TAHFIDZ DALAM PENGEMBANGAN KARAKTER SISWA - Nur Rohmah; Tatik Swandari (LP3M STIT Al Urwatul Wutsqo Jombang, 2021)
The purpose of this article is to analyze and describe the planning, implementation, and evaluation of Al-Qur'an tahfidz learning in the tahfidz program in developing student character at MTs Al-Arqom Sarirejo, Balen, Bojonegoro Regency. This research is a field research using a qualitative descriptive approach. This research was carried out at MTs Al-Arqom Sarirejo. The time of this research was carried out in April-July 2021. The subjects of this study were the head madrasah, vice chairman of the curriculum, tahfidz teachers, homeroom teachers, students and guardians of students. Data collection techniques using interviews, observation, and documentation. The data validity technique uses triangulation of sources and methods. The data analysis technique uses an interactive analysis model, which consists of data reduction, data presentation and conclusion drawing. The results showed that: 1) Tahfidz Qur'an learning strategies carried out at MTs Al-Arqom were: a) talaqqi, namely feedback between teachers and students. b) takrir, namely memorizing with the guidance of the teacher and deposited with the teacher. c) muroja'ah, namely by repeating memorization together with other students. d) mudarosah, that is, students memorize by taking turns with other friends. e) the test, namely, the memorization test to determine the fluency of the students' memorization. 2) The implementation of the tahfidz Al-Qur'an learning strategy is able to change the character of students for the better. The characters that stand out are: religious, honest, disciplined, independent, responsible, clean, istiqomah, patient, polite.